Perkecambahan Biji Dan Pertumbuhan Bibit Batang Bawah Karet (Havea brasiliensis Muell Arg.) Dari Klon Dan Media Yang Berbeda - Devi Sara; Munifatul Izzati; Erma Prihastanti (Jurnal Akademika Biologi, 2014)
Rubber tree is an economical plant because of its latex production which is used as raw materials in rubber industries. The most important steps in rubber tree cultivation are germination and nurseries of stock for the grafting. The aims of the study to investigate seed germination from  3 types of clone and stock growth from different clone and plant media. The research consists of two steps: 1. to investigate seed germination from 3 types of clone, 2. to investigate growth of stock rubber on different clone and plant media for 30 days. The study design used completely randomized design (CRD) with 4 repetition. The first factor was plant media (soil, soil + manure, soil + liquid fertilizer, soil + ash). Second factor was seed clone (PB 260, GT 1, BPM 24). The pameter measured were germination percentage, stem height, root length, leaf number, leaf area, dry and fresh weight. Collected data were analyzed by Analysis of Variance (ANOVA) continued by Duncan Multiple Range Test (DMRT) in 95% significance difference. The study resulted that BPM 24 clone had the highest germination percentage on 74,9%, while PB 260 is 71% and GT 1 is 63,6%. The types of clone affected on growth of stock rubber tree. The PB 260 clone had better stem height, root length, leaf number, leaf area, dry and fresh weight parameter than the other clone. Plant media had no effect on all parameters. There is no interaction between plant media clone in affecting to growth of stock rubber.Key Words: Clone, PB 260, GT 1, BPM 24, manure, liquid fertilizer